The Reindeer Botanist: Alf Erling Porsild, 1901–1977 - Dathan, Wendy (University of Calgary Press, 2012)
Series: Northern Lights Series; 14 This well-researched book is the first biography of one of Canadas most remarkable botanists. Alf Erling Porsild (1901-1977) grew up on the Arctic Station in West Greenland and later served as curator of botany at the National Museum of Canada. He collected thousands of specimens, greatly enlarging the National Herbarium and making it a superb research centre. For nearly twenty years, Porsild studied reindeer activities in Alaska and the Northwest Territories as part of the Reindeer Project designed to encourage grazing animal husbandry among aboriginal peoples. He published extensively, and his meticulous research and observations have particular relevance today with the growing concern over global warming in the Arctic. Yes This book has been published with the help of a grant from the Canadian Federation for the Humanities and Social Sciences, through the Aid to Scholarly Publications Program, using funds provided by the Social Sciences and Humanities Research Council of Canada.